The Influence of End-of-Day Blue Light on the Growth, Photosynthetic, and Metabolic Parameters of Lettuce at Different Development Stages - Viktorija Vaštakaitė-Kairienė; Giedrė Samuolienė; Vaidevutis Šveikauskas; Kristina Laužikė; Sigita Jurkonienė (Plants, 2022)
This study evaluates the effect of end-of-day blue (EOD B) light on the physiological response of lettuce (Lactuca sativa, Lobjoits Green Cos) at different phenological development stages. Plants were grown in a controlled environment growth chamber (day/night temperature 21 ± 2 °C; relative air humidity 60 ± 5%) under the light of light-emitting diodes (LEDs) consisting of 5% blue (B; 450 nm), 85% red (R; 660 nm), and 10% green (G; 530 nm) photosynthetic photon flux density (PPFD) at 200 µmol m−2 s−1 for 16 h d−1 (BRG, control) for 8, 15, and 25 days (BBCH 12, BBCH 14, and BBCH 18, respectively). For the EOD B treatments, lettuce plants were additionally illuminated with 100% of B light at 30 and 60 µmol m−2 s−1 PPFD for 4 h d−1 (B30 and B60, respectively). The results show that EOD B light caused the elevated shoot elongation of lettuce plants regardless of their growth stages. However, leaf width increased only in more developed lettuce plants (BBCH 18). EOD B light negatively affected the development of new leaves and fresh weight, except for seedlings (BBCH 12). Most photosynthetic and spectral leaf indices also decreased when lettuce was treated with EOD B light, especially under the PPFD level of 60 µmol m−2 s−1. Moreover, the changes in metabolic parameters such as DPPH free radical activity, free proline content, and H+-ATPase activity in lettuce showed a plant response to unfavorable conditions to EOD B light.